Influence of browse availability of goats diets in an Acacia senegal savannah of South- Central Kenya. - Kamau, P.N. (Texas A&M University, 1985)
Seasonal effect of bush canopy on dietary selection and nutrition of goats was evaluated at Kiboko, south-central Kenya from June through November, 1982. Three mature esophageally fistulated East-African goats were used in the study on a one day graze, 28-30 day rest cycle. Treatment paddocks (2.25 ha), twice replicated were established in three bush conditions designated as light, moderate, and heavy with 13.1,30.7 and 46.8% total canopy cover, respectively. Dietary habits of the goats reflected a high degree of seasonal flexibility between forag~_~lasses, species and plant .parts. Grass and grasslike species dominated goat diets in the early-dry period, particularly Cencnrus ciliaris, Sporobolus pellucides, Eragrostis caespitosa, Digitaria macroblephara and Chloris roxburghiana. Talinum portulacifolium, which dominated the forb category, became an important component in the diet composition in the early wet season. Overall, browse played the most important role in the diets of goats mainly in the moderate and heavy bushed treatment paddocks from August through November. Acacia senegal pods were the major source of food for goats in July and August. Grasses, forbs and woody species comprised 45%, 7% and 47% of goat diets respectively throughout the study period. Leaves, stems and fruits (seeds, pods and grass inflorescences) from all categories of vegetation iv were consumed by goats. However, leaves formed the greatest portion of, the goat diets throughout the period of study. Solanum incanum, Grewia bicolor, Acacia mellifera, Acacia senegal, Cenc~~s ciliaris and Sporobolus pellucides were the most preferred woody and grass species during the early-dry and late-dry seasons while Talinum portulacifolium, Solanum incanum, Acacia mellifera, Commiphora africana, Sporobolus pellucides and Chloris roxburghiana were the most preferred vegetation species in the early-wet season. Nutritional analysis of extrusa indicated that the goats were able t to select diets adequate in protein to meet maintenance requirements throughout the period of study. A potential energy deficiency for maintenance was noted in moderate and heavy bushed conditions in August and heavy bushed conditions in September.